The Central Bank Governor and Interest Rate Setting by Committee - Emile van Ommeren; Giulia Piccillo (Center for Economic Studies and ifo Institute (CESifo), 2019)
This paper examines the role of central bank governors in monetary policy decisions taken by a committee. To carry out this analysis, we constructed a novel dataset of committee voting behaviour for six OECD countries for up to three decades. Using a range of Taylor-rule specifications, we show that a change in governor significantly affects the interest rate setting of the whole committee. We also observe systematic differences in the responsiveness to recent changes in the state of the economy based on the political party appointing the governor, with higher responsiveness under governors that are appointed by a left-wing political authority. In contrast, right wing appointed governors are more likely to consider expected economic developments in the future when deciding on the appropriate interest rate.
Keywords: E00; 330; monetary policy; Taylor rule; central bank governors